Breaking the low pay, no pay cycle: The effects of the UK Employment Retention and Advancement programme - Richard Hendra; James Riccio; Richard Dorsett; Philip Robins (IZA Journal of Labor Policy, 2015)
This paper presents the final economic results of the UK Employment Retention and Advancement (ERA) programme. ERA's distinctive combination of post-employment advisory support and financial incentives was designed to help low-income individuals who entered work sustain employment and advance in the labour market. ERA targeted three groups. ERA produced short-term earnings gains for two lone parent target groups. However, these effects generally faded after the programme ended, largely because the control group caught up with the ERA group. For the New Deal 25 Plus target group (mostly long term unemployed men), ERA produced modest but sustained increases in employment and earnings.
Keywords: I38; J18; C93; 330; Financial incentives; Welfare-to-work; Long term unemployed; Field experiment